Problemy skupu mleka w Okręgowej Spółdzielni Mleczarskiej Limanowa - Kosowski, Bronisław; Kosowski, Piotr (Problems of Milk Purchase in District Milk Cooperative of Limanowa within 1990-2004, 2005)
The analysis of the level of milk purchase in district milk cooperative of Limanowa allows for the observation of a severe crisis in this area within the period of 1990 - 1995 (nearly 50% reduction). On the contrary, since 1996 the level of milk purchased has gradually increased reaching in 2004 the amount of 1/4 higher than the level of 1990. Abilities of the cooperative discussed in the paper testify that the amount of milk purchased till 2007 may increase by 50%.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 473-477